Rola planowania strategicznego w dokumentowaniu zakładowych zasad rachunkowości i operacji gospodarczych - Hasik, Wojciech (The Role of Strategic Planning in the Area of Documenting of Accounting Policies and Accounting Events, 2005)
The true and fair presentation concept is not an objective feature of accounting. It depends on variety of factors. However, the most important of them id the company’s goal - its strategic plan. As a result the economic substance of most accounting events has got no universal, objective meaning. Instead, the presentation of those accounting events must consider the impact they have on the achievement of company’s goal. Therefore, the goal context approach must be applied into creating the entity’s accounting policies (the system level solutions) as well as documenting the single accounting event (ad hoc solutions). The evidence and informative function of accounting is not achievable until the company’s accounting policie’ (particularly decisions related to assets and liabilities recognition, measurement, disclosure and presentation) are clearly connected to its strategic plan.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 15-21